Effects of Melatonin on Hepatic and Renal Complication of Diabetes - Hamed Safarzadeh; Felor Zargari (Fasa University of Medical Sciences, 2022)
Background & Objective: Diabetes is associated with biochemical and pathological changes in liver and kidney tissue. One of the most important mechanisms in causing   complications of diabetes is increasing the production of free radicals due to impaired glucose metabolism. Some studies have shown that melatonin is effective in protecting tissues due to its antioxidant role. The aim of this study was to evaluate the effect of melatonin on biochemical factors, histopathological changes of liver and kidney in streptozotocin-induced (STZ) diabetic rats. Materials & Methods: In this experimental study, 40 adult male rats were randomly divided into 4 groups (n=10): control group, diabetic group, melatonin group (20mg/kg BW) and melatonin + diabetic group.  At the end of the 6th week, blood samples were collected. Biomarkers of liver function (alkaline phosphatase: ALP, aspartate aminotransferase: AST, alanine aminoteransferase: ALT) and kidney biomarkers (urea, uric acid, BUN, creatinine), serum glucose and histopathological changes of these tissues were evaluated.  Data analysis was performed using SPSS and the significance level was P<0.05. Results: Melatonin treatment significantly (P<0.05) reduced hyperglycemia, hepatic enzymes and renal biochemical factors due to diabetes and improved histopathological changes of liver and kidney tissue. Conclusions: Melatonin consumption can be effective in improving the renal and kidney complications of diabetes.